PENGARUH BELANJA PEMERINTAH SEKTOR INFRASTRUKTUR PUBLIK DAN SEKTOR BANTUAN OPERASIONAL KESEHATAN TERHADAP PERTUMBUHAN EKONOMI DI KAWASAN INDONESIA BAGIAN TIMUR - Sky, Monica Werin; Azwardi, Azwardi (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2023)
This study aims to analyze the effect of government spending on the public infrastructure sector and the health operational assistance sector on economic growth in the provinces of Eastern Indonesia in 2017-2021. This study uses secondary data in the form of panel data from 2017-2021, which are sourced from the Central Bureau of Statistics and the Director General of Fiscal Balance, Ministry of Finance of Indonesia. The method used is quantitative descriptive analysis using panel data regression analysis techniques using Eviews 9 software. The results show that government spending in the public infrastructure sector has a positive and significant effect on economic growth. Meanwhile, government spending in the health operational assistance sector has a negative and significant effect on economic growth.